An Overview of Medicinal Plant of Tinospora Cordifolia - Sadgir Gayatri L.; Shinde Prajkta.P (Asian Journal of Pharmaceutical Research and Development, 2026)
Tinospora cordifolia, or “Guduchi” or “Giloy,” is a big deciduous climbing shrub belonging to the family Menispermaceae. With genetic variability. it is extremely widespread in india and neighbouring countries and thrives in tropical areas. it is gently valued traditional medicines, especially Ayurveda, owing to its broad-spectrum therapeutic properties. The plant is characterized morphologically by its coiling branches, fleshly stem, heart-shaped leaves, racemose inflorescences, curved seeds, and aerial roots with special tetra- to penta-arch vascular patterns.Here in this review, explores the genetic diversity, morphological features, chemical composition, and medicinal value of T. cordifolia. Various are considred.some of the bioactive constituents such as alkaloids, glycosides, diterpenoid lactones, steroids, phenolics, and polysaccharides have been reported from its root, stem, leaves, and whole plant. These molecules are accountable for wide range of pharmacological activities including anti-diabetic, antioxidant, anti-inflammatory, immunomodulatory, hepatoprotective, anti-stress, anti-allergic, anti-microbial, and anti-cancer effect. Ethnopharmacological confirmation establishes its efficacy in curing of dieases including diabetes, fevers, respiratory diseases, liver abnormalities, dermatological disorders, and cognitive dysfunction. There is also existing pharmacological evidence of its adaptogenic and immunostimulatory effects and incresing interest towards its anticancer activity l. This present review discusses available information on T. cordifolia, calling attention to its clinical importance and likely applications within both traditional and modern medicine.